Family-based genetic association study of CNTNAP2 polymorphisms and sociality endophenotypes in Korean patients with autism spectrum disorders. (February 2017) - Yoo, Hee Jeong; Kim, Boong-Nyun; Kim, Jae-Won; Shin, Min-Sup; Park, Tae-Won; Son, Jung-Woo; Chung, Un-Sun; Park, Mira; Kim, Soon Ae
Abstract : Supplemental Digital Content is available in the text.